Implementation Gap in Girl Child Protection Laws in India: A Critical Socio-Legal Analysis - Meena, Mahendra Singh; Agarwal, Sushma (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
In India, the protection of girl children is part of the Constitution’s guarantee of equality, dignity and social justice. Since independence, India has built an extensive legal structure to support efforts at eliminating structural discrimination (including against girls), sexual exploitation, child marriage, trafficking and gender-based practices. The Constitution provides guarantees (Articles 14, 15, 21) and supports these guarantees with Directive Principles of State Policy: these articles provide the normative basis on which State intervention for-protecting girl children can be based. Many Acts (including the Protection of Children from Sexual Offences Act, 2012 (POCSO), Prohibition of Child Marriage Act, 2006 (PCMA), Pre-Conception and Pre-Natal Diagnostic Techniques Act, 1994 (PCPNDT) and Juvenile Justice (Care and Protection of Children) Act, 2015) implement these Constitutional guarantees. However, there continues to be a large gap between implementation and the law, as shown by inadequate national crime data, demographic surveys, and peer-reviewed socio-legal studies. Although these -laws are well designed (by international standards), enforcement is uneven across States and regions. Based on a doctrinal analysis of law and socio-legal examination of national databases and recent academic studies this paper concludes that the main reason for this disparity lies in structural patriarchal systems in India, fragmentation of institutions, delays in procedures, and socio-economic disadvantages that limit enforcement. As such, the study will explore the constitutional philosophy, legislative development, judicial interpretation and obstacles to governance around establishing substantive equality for girl children in India.